ANALISIS DAN DESAIN SISTEM APLIKASI PENJADWALAN KULIAH PENGGANTI (RESCHEDULE-IN) BAGI MAHASISWA DAN DOSEN DI UNIVERSITAS - Amaliyah, Putri; Aulia, Putri Faza; Akbar, Muhammad Farhan; Maulidana, Royhan Aditya; Safitri, Anita (Journal of Digital Business and Innovation Management, 2023)
The process of scheduling replacement classes is a crucial activity in a university environment. This task is performed when events occur that result in the cancellation of scheduled classes, such as a teacher’s unavailability, emergency situations, and others. The manual approach to scheduling replacement classes often takes a long time, lacks efficiency, and is prone to errors. Therefore, an efficient system for scheduling replacement classes is needed. The Object-Oriented Analysis and Design (OOAD) methodology is used for the analysis, which includes various diagrams such as use case diagrams, use case scenarios, sequence diagrams, and activity diagrams.